Dynamic Model of MR Dampers Based on a Hysteretic Magnetic Circuit. (3rd April 2018) - Guo, Pengfei; Xie, Jing; Guan, Xinchun
Abstract : As a key to understand dynamic performances of MR dampers, a comprehensive dynamic magnetic circuit model is proposed in this work on the basis of Ampere's and Gauss's laws. It takes into account not only the magnetic saturation, which many existing studies have focused on, but also the magnetic hysteresis and eddy currents in a MR damper. The hysteresis of steel parts of MR dampers is described by Jiles-Atherton (J-A) models, and the eddy current is included based on the field separation. Compared with the FEM results, the proposed model is validated in low- and high-frequency studies for the predictions of the magnetic saturation, the hysteresis, and the effect of eddy currents. A simple multiphysics model is developed to demonstrate how to combine the proposed magnetic circuit model with the commonly used Bingham fluid model. The damping force in the high-frequency case obviously lags behind the coil current, which exhibits a hysteresis loop in the current-force plane. The lag of damping force even exists in a low-frequency varying magnetic field and becomes more severe in the presence of eddy currents.